LuaTV: uma api para extensão de aplicações No ambiente Ginga-NCL - Brandão, Rafael Rossi de Mello (2010)
The Ginga-NCL environment is responsible for the presentation of declarative (NCL) applications on the Brazilian Digital TV System (SBTVD), and it is also the ITU-T H.761 Recommendation for IPTV middleware. Lua is the scripting language of NCL. ITU-T H. 760 series also defines two sets of NCLua API for the development of IPTV applications: the Core and the Extended API. The Core comprises the basic NCLua API, which are part of the Ginga-NCL original specification for the Brazilian terrestrial DTV system. The Extended aims to provide other relevant functionalities incorporating some of the features commonly present on other imperative environments. This work aims to present a set of Lua APIs named LuaTV, which will be part of the draft specification for the NCLua Extended API. LuaTV features are divided into four functional categories: metadata, with functionalities related to the accessing Digital TV metadata information; security, providing mechanisms for encrypting and authenticating data; multidevices, offering high-level access to resources commonly available on remote devices; and widget, aimed at graphical support to applications.